Radiographic adenoid evaluation - suggestion of referral parameters - Murilo F.N. Feres; Juliana S. Hermann; Ana C. Sallum; Shirley S.N. Pignatari (Elsevier, 2014)
Objective: this study aimed to evaluate the usefulness of current radiographic measurements, which were originally conceived to evaluate adenoid hypertrophy, as potential referral parameters. Methods: children aged from 4 to 14 years, of both genders, who presented nasal obstruction complaints, were subjected to cavum radiography. Radiographic examinations (n = 120) were evaluated according to categorical and quantitative parameters, and data were compared to gold-standard videonasopharyngoscopic examination, regarding accuracy (sensitivity, negative predictive value, specificity, and positive predictive value). Results: radiographic grading systems presented low sensitivity for the identification of patients with two-thirds choanal space obstruction. However, some of these parameters presented relatively high specificity rates when three-quarters adenoid obstruction was the threshold of interest. Amongst the quantitative variables, a mathematical model was found to be more suitable for identifying patients with more than two-thirds obstruction. Conclusion: this model was shown to be potentially useful as a screening tool to include patients with, at least, two-thirds adenoid obstruction. Moreover, one of the categorical parameters was demonstrated to be relatively more useful, as well as a potentially safer assessment tool to exclude patients with less than three-quarters obstruction, to be indicated for adenoidectomy. Resumo: Objetivo: o objetivo deste estudo foi de investigar a utilidade de medidas radiográficas destinadas à avaliação da tonsila faríngea a serem utilizadas como potenciais parâmetros de encaminhamento. Métodos: crianças de quatro a 14 anos, de ambos os gêneros, que apresentavam queixas referentes à obstrução nasal foram submetidas à radiografia do cavum. Os registros radiográficos (n = 120) foram avaliados de acordo com parâmetros categóricos e quantitativos, e dados resultantes foram comparados ao exame padrão-ouro de videonasofaringoscopia, em relação às suas taxas de acurácia (sensibilidade, valor preditivo negativo, especificidade e valor preditivo positivo). Resultados: os parâmetros radiográficos categóricos apresentaram baixa sensibilidade para a identificação de pacientes portadores de ⅔ de obstrução do espaço coanal. No entanto, alguns destes parâmetros apresentaram especificidades relativamente altas quando ¾ de obstrução coanal era o ponto de corte de interesse. Dentre as variáveis quantitativas, um modelo matemático se mostrou mais adequado para identificar pacientes com mais de ⅔ de obstrução coanal. Conclusão: este modelo demonstrou, assim, ser potencialmente útil como método de rastreamento para identificação de pacientes com pelo menos ⅔ de obstrução adenoidiana. Além disso, um dos parâmetros categóricos analisados demonstrou ser relativamente mais útil e potencialmente seguro para eliminar pacientes queixosos com menos de ¾ de obstrução a serem indicados à adenoidectomia. Keywords: Mouth breathing, Diagnosis, Adenoidectomy, Palavras-chave: Respiração bucal, Diagnóstico, Adenoidectomia